Lifestyle Choices and Brain Health - Mintzer, Jacobo; Donovan, Keaveny Anne; Kindy, Arianne Zokas; Lock, Sarah Lenz; Chura, Lindsay R.; Barracca, Nicholas (Frontiers in Medicine, 2019)
This article is largely based on the recommendations of the AARP's Global Council on Brain Health (GCBH) and aims to provide an overview of evidence from current literature and expert opinion on key elements known to be relevant in preserving brain health as people age. Although we realize that there may be other lifestyle choices of importance to brain health, the GCBH has decided to initially focus on the issues below based on the preferences and concerns of its members. The areas to be discussed are: mental well-being, exercise, cognitively stimulating activities, sleep, nutrition, and social connectedness. Our review concluded that each of these areas offer opportunities for aging individuals to make lifestyle adjustments to positively impact brain health.